Strategi Adaptasi Komunitas Sedulur Sikep di Desa Klopoduwur Blora pada Era Globalisasi - Nurmalya Ayu Dyani; Yuhastina; Nurhadi (Paradigma: Jurnal Kajian Budaya, 2022)
The sedulur sikep community is a collection of individuals who practice the sedulur sikep teachings, which contain the noble values of life, such as the value of humanity, the value of love for the homeland, and the value of love for the universe. The sedulur sikep community also has traditions and customs as its local wisdom. Globalization marked by the development of science and technology causes changes in various aspects of the life of the sedulur sikep community, such as changes in the religious system, changes in increasingly modern technology, and changes in traditions or customs. This article aims to explain the changes in the era of globalization and explain the adaptation strategies carried out by the sedulur sikep community in Klopoduwur Village to deal with these changes. This study uses qualitative research methods with descriptive-analytical writing presentations. The results of this study indicate that the sedulur sikep community in Klopoduwur Blora Village adapts in the era of globalization through 1) acculturating religious elements, 2) internalizing the teachings of sedulur sikep, 3) establishing traditional institutions, 4) associative social interactions with outsiders, and 5) technology limitation. When facing the current globalization, the sedulur sikep community is diffusing innovations related to the religious system and the use of advanced technology in various fields of life. Although in the diffusion process, several innovations are accepted, some innovations are limited as a form of self-defence so that the teachings of sedulur sikep remain sustainable.